Description of Growth and Development of Children Aged 1-3 Years with a History of Low Birth Weight Babies - Wahyuti, Wahyuti; Pariaribo, Konstantina M; Rukayah, Siti; Iriani, Restu; Malaha, Naomi; Fitria N, Revie; Suminar, Saka (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Growth is an increase in the size and number of cells and intercellular tissue, meaning an increase in the physical size and structure of the body in part or in whole, so that it can be measured in units of length and weight. Development is a change that is both quantitative and qualitative, namely increasing the ability (skills) of more complex body structures and functions, including the development of cognitive, language, motor, emotional and behavioral development. The purpose of this study was to find out the description of growth and development in children aged 1-3 years with a history of Low Birth Weight Babies. This study used a descriptive research method using a cross-sectional approach. The total population is 30 toddlers at the Sudiang Health Center. So the number of samples in this study were 30 people. The sampling technique used in this research is total sampling. Data collection was carried out by distributing questionnaires and distributing observation sheets. The results of this study are a picture of growth and development in children aged 1-3 years, there are characteristics of the child, the sex of the child, parents' education and parents' economic status. there is a history of Low Birth Weight Babies with child development 1-3 years. In conclusion, there is a picture of growth and development in children aged 1-3 years, there are characteristics of the child, the sex of the child, parents' education and parents' economic status. There is a history of Low Birth Weight Babies with child development 1-3 years.